A Mine Ventilation System Energy Saving Technique Based on an Improved Equilibrium Optimizer - Yu, Bao-cai; Shao, Liang-shan (Frontiers in Energy Research, 2022)
With the continuous increase of the mining years of the coal mine, the ventilation system has become more and more complex. Due to the lack of scientific and effective management, the ventilation system energy consumption has increased rapidly, resulting in serious energy waste. In order to solve this problem, the author established a nonlinear optimization model aiming at minimizing the total energy consumption of mine ventilation network. Furthermore, the author proposed an improved equilibrium optimizer algorithm to solve the model. First, the population is initialized by chaotic map. Second, the adjustment strategy of trigonometric function is introduced to improve the index , which improves the global development ability of the algorithm, avoids falling into local optimum, can improve the local search ability in the later stage. And then the introduction of Gaussian disturbance to enhance the diversity of particles and avoid falling into local optimum. Finally, we introduced a learning factor to improve the generation rate , improve the algorithm's integrity, and compare it with other algorithms. The simulation results show that the performance of the improved algorithm is significantly better than other algorithms. We test the ventilation system of Wangjialing mine of Zhongmei Huajin Energy Co. Ltd.. The result shows that the energy consumption of the ventilation system is reduced by 17.83%. This method can save about 2000000 yuan RMB every year. The economic effect is remarkable, we achieve the purpose of energy conservation and emission reduction, and the effectiveness of the proposed method is verified.